2002
DOI: 10.1038/nature00815
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Arabidopsis cryptochrome 2 by blue-light-dependent phosphorylation

Abstract: Cryptochromes are blue/ultraviolet-A light receptors that mediate various light responses in plants and animals. But the initial photochemical reaction of cryptochrome is still unclear. For example, although most photoreceptors are known to undergo light-dependent protein modification such as phosphorylation, no blue-light dependent phosphorylation has been reported for a cryptochrome. Arabidopsis cryptochrome 2 (cry2) mediates light regulation of seedling development and photoperiodic flowering. The physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
212
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 28 publications
16
212
0
1
Order By: Relevance
“…However, the level of phosphorylation detected speaks against an unspecific overphosphorylation as found, for example, in rhodopsin in vitro (50). Autophosphorylation has already been demonstrated for full-length AtCRY1 and AtCRY2 in vitro and in vivo (21,22,51) despite the fact that they do not contain sequence similarities to any known kinase. It is closely associated with the function or regulation of the receptors (22,51).…”
Section: Discussionmentioning
confidence: 98%
“…However, the level of phosphorylation detected speaks against an unspecific overphosphorylation as found, for example, in rhodopsin in vitro (50). Autophosphorylation has already been demonstrated for full-length AtCRY1 and AtCRY2 in vitro and in vivo (21,22,51) despite the fact that they do not contain sequence similarities to any known kinase. It is closely associated with the function or regulation of the receptors (22,51).…”
Section: Discussionmentioning
confidence: 98%
“…It seems that cryptochromes have conserved the photoactivation part of the photolyase photochemistry but accumulate the flavin radical instead of fully reduced flavin and use this process for signaling, most likely by conformational changes in their C-terminal output domains that are sufficient for Cry signaling (47,48). This work, together with studies on light-driven electron transfer (17), phosphorylation (34,49,50), and dimerization (48) of cryptochromes provides a foundation for analyzing in detail the early events in the light activation and signal transduction of plant cryptochromes.…”
Section: Discussionmentioning
confidence: 99%
“…Cry2 is degraded in vivo when irradiated with blue light, most likely resulting from direct absorption of light by Cry2 followed by proteasomal degradation (28,34). To determine whether the above described photoreversible responses were also reflected in the stability of Cry2, we analyzed Cry2 protein levels under the same conditions as for the quantification of FT transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Quite often, the phosphorylation state of a given protein alone determines the "on/ off" state of a given signaling process (51-54). In this regard, it is intriguing to note that the three major morphogenic photoreceptor types in plants (cryptochrome, phytochrome, and phototropin) exhibit protein kinase activity (4,(55)(56)(57)(58)(59)(60)(61) and that protein phosphorylation/ dephosphorylation events are associated with their signaling pathways (5,(62)(63)(64)(65)(66). In this study, we have demonstrated that the phot1-interacting protein NPH3 is a phosphoprotein in etiolated seedlings and that the BL-induced dephosphorylation of this protein may be necessary for phot1-dependent phototropic signaling.…”
Section: Discussionmentioning
confidence: 99%